2014
DOI: 10.22226/2410-3535-2014-4-315-318
|View full text |Cite
|
Sign up to set email alerts
|

Properties of discrete breathers in 2D and 3D Morse crystals

Abstract: Based on the results of molecular dynamics simulations the characteristics of discrete breathers (DB) in two-dimensional (2D) and three-dimensional (3D) crystals with Morse long-range interatomic interactions are compared. It is demonstrated that DB in 3D crystal have higher frequencies and higher degree of localization than in 2D crystal.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
5
0
2

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 33 publications
0
5
0
2
Order By: Relevance
“…We considered the value α = 5, for which the equilibrium interatomic distance is a = 0.98813 at the potential cutoff radius of 5.5a. We note that the Morse potential was often used for the simulation of different properties of discrete breathers in crystals [23][24][25][26][27][28][29][40][41][42][43][44][45][46].…”
Section: Nonlinear Phenomenamentioning
confidence: 99%
See 1 more Smart Citation
“…We considered the value α = 5, for which the equilibrium interatomic distance is a = 0.98813 at the potential cutoff radius of 5.5a. We note that the Morse potential was often used for the simulation of different properties of discrete breathers in crystals [23][24][25][26][27][28][29][40][41][42][43][44][45][46].…”
Section: Nonlinear Phenomenamentioning
confidence: 99%
“…The authors of [38] could excite only the discrete breathers with the soft type of nonlinearity, considering a diatomic chain with a gap in the phonon spectrum. It was shown later that discrete breathers with the hard type of nonlinearity can exist in two-and threedimensional crystals with Morse interaction [39][40][41][42][43][44][45][46]. The reason is that the effect of the increase in the average interatomic distances in the core of the discrete breathers can be suppressed to some extent in crystals of dimension higher than unity and, thus, the hard core of the interatomic potential makes a larger contribution to the dynamics of the system than the soft tail.…”
mentioning
confidence: 99%
“…By now, a large volume of works has been performed to analyze properties of DB in various crystalline materials, particularly, the results of the molecular dynamics studies have been reported in . Several works have been devoted to the study of DB in model crystals with Morse interatomic potentials [4][5][6][7], while other works to the study of DB in graphene and related materials [8][9][10]. In the work [8], for the first time, DB in a crystalline body has been studied with the help of DFT theory, using graphane as an example.…”
Section: Introductionmentioning
confidence: 99%
“…/ Письма о материалах 5 (1), 2015 стр. [11][12][13][14] Semenov et al / Letters on materials 5 (1), 2015 pp. 11-14 дах физических систем, включая оптические, механиче-ские, электрические, атомные и др.…”
unclassified
“…В классических работах по изучению ДБ рассматри-вались модельные дискретные системы низкой размер-ности с простейшими видами ангармонизмов в меж-частичных взаимодействиях [1][2][3] и были развиты аналитические и полуаналитические методы построе-ния бризерных решений, изучены их основные свойства. В настоящее время растет число работ по исследованию ДБ в различных кристаллических материалах [4][5][6][7][8][9][10][11][12][13][14][15], что требует существенного уточнения рассматриваемых моделей.…”
unclassified